Strategi Guru dalam Menanggulangi Perundungan pada Anak Kelas V - Dwi Yani P; Achmad Sultoni; Oktaviani Adhi Suciptaningsih (Pusat Riset dan Inovasi Nasional, 2023)
Bullying students in schools is one of the three great sins of education. This is the concern of researchers to conduct this research. The purpose of this research is to show how teacher learning strategies can reduce student bullying. With a case study design, descriptive qualitative research used is observation, interviews with teachers and students, and documentation is the method used to collect data. Data is reduced, presented, and analyzed by drawing conclusions. Member checks, technical triangulation, and source triangulation are methods used to verify data validity. The research was conducted at a public elementary school in Mojokerto Regency which involved 3 teachers who taught grade 5, namely Class Teachers, Religious Education Teachers and PJOK Teachers and 23 Grade V students. This research was conducted on December 7, 2022. The research results found that the methods used by classroom educators to deal with bullying in schools are 1) planning with teachers and student guardians, 2) instilling Pancasila values, 3) innovation in learning, and 4) using directing and directing administration. Based on these findings, it can be concluded that strategies for dealing with student bullying work best when parents work well together to deal with it.